Prioritizing Nutrition in Agriculture and Rural Development : Guiding Principles for Operational Investments - Herforth, Anna; Jones, Andrew; Pinstrup-Andersen, Per (World Bank, Washington, DC, 2013)
Agricultural and rural development provides a critically important opportunity for reducing malnutrition. The purpose of this paper is to provide a set of guiding principles for incorporating nutrition goals into the design and implementation of agricultural and rural development projects, and to provide examples of current best evidence options for operational investments. Several principles are likely to be important in all or most cases for nutrition-sensitive agriculture, which can be adapted to individual contexts. These include the following: 1) incorporate nutritional concerns into the design and implementation of agricultural policies, projects, and investments; 2) target nutritionally vulnerable groups; 3) invest in women; 4) increase year-round access to diverse, nutrient-dense foods; 5) protect health through water management; 6) design poverty-reduction strategies explicitly to benefit nutrition; 7) create enabling environments for good nutrition through knowledge and incentives; and 8) seek opportunities to work across sectors. To help assess which actions are most relevant for a specific situation, a set of key questions are included after each broad principle. The paper also highlights areas where agricultural investments may cause harm, and provides options for improving policy coherence. The principles underscore investments in people and systems that have the potential to transform underlying conditions and positively influence the multiple, proximal determinants of proper nutrition. Further research and evaluation priorities include tracking impact on multiple outcomes at once (such as diet, nutritional status, productivity, and income); designing studies that can attribute impact to specific approaches; and collecting information on costs and cost-effectiveness. Although there is a need to strengthen knowledge around design and implementation strategies, there is good evidence that well-planned investments are likely to reach at least targeted income and dietary outcomes. Existing knowledge around the recommended principles is sufficient to move ahead in designing nutrition-sensitive agricultural interventions.